THE ROLE OF COMPETENCY AND JOB PLACEMENT IN IMPROVING THE PERFORMANCE OF EMPLOYEES AT THE GORONTALO CITY EDUCATION OFFICE - Sampow, Glady Christina; Machmud, Rizan; Monoarfa, Mohamad Agus Salim (Universitas Negeri Gorontalo, 2026)
This research is motivated by key performance issues among employees of the Gorontalo City Education Office, particularly related to low efficiency and consistency in services, weak work discipline, and suboptimal utilization of human resources. The purpose of this research was to measure and analyse the influence of competence and job placement on employee performance at the Gorontalo City Education Office. It employed a quantitative approach with multiple linear regression analysis. The sample consisted of 33 respondents who are employees of the Education Office. Data collection was conducted using questionnaires with a semantic differential scale. Based on the F-test results, the significance value obtained was 0.029, which is lower than 0.05, indicating that the independent variables simultaneously have a significant effect on the dependent variable. Partially, the results also show that competence and job placement both influence employee performance at the Gorontalo City Education Office. Furthermore, the R² value obtained is 0.545 (54.5%), indicating that 54.5% of employee performance is significantly influenced by competence and job placement, while the remaining 45.5% is attributed to other factors outside the scope of this research model.